Household energy conservation behaviour: A socio-economic perspective - Adeyemi Adepoju; Kayode Ekundayo; Abiodun Oladiipo (Journal of Digital Food, Energy & Water Systems)
Studies on energy conservation and household behaviour were predominantly based on econometrics using secondary data with limited studies employing the primary data. In addition, the use of secondary data from developing countries are not without their inadequacies due to missing data points. However, generating data may lead to over or under estimations which led to this study deploying structural equation model and making use of cross-sectional data from a developing country perspective. Data were collected through a structured questionnaire from 329 respondents in Akure Metropolis households, Nigeria, that were selected using a random sampling techniques. The study adopted the Partial Least Square Structural Equation Modelling approach. The results of the study showed that socio-economic variables electricity price, household size, income, number of appliance and weather have significant effects on energy conservation behavior with income having the largest structural weight. This implies that income is of utmost importance to residents` electricity saving practices as householders consume more and save less electricity with more income.  It is therefore recommended that energy conservation policy should aim at regulating the purchase of electricity units at household levels, where the rich pay more tax than the poor. This will foster energy saving improvement at households sector of the Nigerian economy.